Comparative Study Between Sentinel Node Biopsy Versus Axillary Sampling in Women with Clinically Node Negative Operable Breast Cancer - P, Pratheeba; .P, Subalakshmi; Balaji MS, Arun; Subburaaj MS, A.P.; MS, J. Sridhar (Journal of Neonatal Surgery, 2025)
Background and Objectives- More recent advance in the field of breast cancer detection at early stage is axillary lymph node sampling, which involves sampling of few lymph nodes removed from axilla for detecting cancerous cells. The aim is to compare the methodologies between sentinel lymph node biopsy and low axillary sampling in predicting status of axillary lymph nodes in clinically node negative operable breast cancer patients. Methodology: A prospective longitudinal study was conducted among 50 breast cancer operable patients with clinically node negative. Axillary sampling was performed first by making a 2 cm incision in the middle third of the proposed axillary clearance incision below the axillary hairline. All axillary fat and tissue in an area of 2cm diameter was dissected out. Results- LAS has a sensitivity of 97.5%, which means it would be able to detect the true positives in 97.5% of the patients and the ability to detect true negatives (specificity) is 64.5%. Similarly, the positive predictive value and the negative predictive value is 91.5% and 89.7% respectively with an accuracy rate of 90%. Conclusion- The results of this study indicate that Sentinel node biopsy and Low axillary sampling are equally accurate. Given the resource and equipment constraints, especially with respect to nuclear medicine facilities, LAS could be the preferred technique in developing countries.